Exploring UK native speaker business professionals' perceptions, attitudes and awareness of the communicative facets of BELF and the communication strategies needed for successful BELF negotiations. - Maslen, Hillary (2015)
BELF (Business English as a Lingua Franca) communication brings together native English Speakers (NSE) and non-native English speakers (NNSE) face to face to do business in today’s culturally and linguistically diverse international workplace. This qualitative inquiry seeks to explore BELF communication from the perspective of the UK NSE business professional and the seemingly problematical role they have in BELF Communication. A case study of five interviews with UK NSE business managers explores and uncovers their perceptions, awareness and attitudes towards the communicative facets of BELF and of the communicative strategies needed for successful BELF negotiations. Analysis of the data reveals that NSE are both aware of the need to accommodate to the other speaker and utilize interactional communication strategies to maintain and deal with the linguistic and cultural challenges that BELF negotiation presents. I make recommendations for the teaching of international business English to be focused on the building of strategic and sociopragmatic competence rather than linguistic competence and to include NSE in this training.